Entrepreneurial Culture of Tourist Area Communities: Case Study on the Fishing Community of Ampiang Parak - Mezy Zulvanita; Lucky Zamzami; Syahrizal Syahrizal (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze the socio-cultural changes in the coastal community of the Nagari Ampiang Parak ecotourism area, which initially relied on fishing for their livelihood, towards a community that leverages natural resources for entrepreneurship. The method used in this research is qualitative ethnography. The research population consists of fishermen living in the Nagari Ampiang Parak ecotourism area, with a sample of local fishermen and entrepreneurs selected through purposive sampling. Data were collected through non-participatory observation, interviews, and documentation. Data analysis was carried out using data reduction, data presentation, and verification techniques. The study results show significant changes in the community's lifestyle, which previously depended on fishing as the primary source of income, and now they are more actively involved in entrepreneurial activities that leverage community-based ecotourism. This study concludes a close relationship between ecotourism development and the community's increased awareness of environmental sustainability and new economic opportunities. The researchers recommend continuous training to enhance the entrepreneurial skills of the local community.